Chapter Il lessico del magistero nelle prose erudite di Giovanni Boccaccio - Fritz, Eleonora (Studi e saggi, 2020)
The contribution aims to illustrate the results of the research conducted on the lexicon of the Petrarch-Boccaccio magisterium relationship. The research also made use of the comparison between Boccaccio's various masters: Petrarch on the one hand, Andalò del Negro and Leonzio Pilato on the other. The results of the research have shown the substantial difference of the Petrarchian magisterium compared to that of Leonzio or Andalò. Petrarch is a supreme teacher unlike the other two, considered by Boccaccio to be technical masters. Boccaccio in fact systematically attributes to Petrarch the noun preceptor, a very generic name: he is considered not only a teacher of literature but also of life. Boccaccio also expects from him a teaching that will lead him to an ethical conversion, as evidenced by the insistent presence of the lexicon pertaining to the moral sphere attributed to him.